Identification of an Inhibitory Mechanism of Luteolin on the Insulin‐Like Growth Factor‐1 Ligand–Receptor Interaction. Issue 8 (29th April 2013) - Yang, Yong; Shen, Jianliang; Yu, Xujiang; Qin, Guoting; Zhang, Mingzhen; Shen, Haifa; Mao, Zongwan; Ferrari, Mauro
<x xml:space="preserve">Abstract</x> Using single‐molecule force measurement and fluorescence imaging, we have demonstrated that luteolin has an inhibitory effect on IGF‐1 ligand–receptor binding, the initial step in IGF‐1 signaling. This inhibition mechanism, which was confirmed by flow cytometry and molecular docking, could play a role in cancer therapy.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>